Efeitos da restrição protéica durante a prenhez sobre a apoptose e a massa de células β pancreáticas - Ramalho, Albina de Fátima Silva (2012)
We investigated the effects of protein restriction during pregnancy on the apoptosis of pancreatic β-cells. Adult rats in the control non-pregnant (CNP) and control pregnant (CP) groups were fed a diet with adequate protein (17%), whereas adult rats in the low-protein non-pregnant (LPNP) and low-protein pregnant (LPP) groups were fed a low-protein diet (6%) for 15 or 20 d. At 15 d, serum prolactin levels in the LPP rats were lower than in the LPNP or CP rats and similar to the levels in the CNP rats. Serum corticosterone levels were higher in the LPP and LPNP rats than in the CP or CNP rats. The low-protein diet increased caspase 3 and Bcl2:Bax mRNA and protein levels independently of physiological status. The levels of caspase 9 protein were higher in islets from the LPP rats than in those from the CP rats. At 20 d, serum corticosterone concentrations were higher in the LPP rats than in the CP or CNP rats. Serum prolactin levels were increased in the LPP and CP rats when compared to the levels in the LPNP or CNP rats. The low-protein diet increased caspase 9 mRNA and protein levels. Caspase 3 protein levels increased in islets from the LPP rats when compared to the other groups. However, amount of β-cell apoptosis in islets from the LPP rats was less than in islets from the LPNP rats, while the latter exhibited less apoptosis than in islets from the CP or CNP rats. β-cell mass did not differ across groups. At concentrations of 2.8 and 8.3 mmol/L glucose, the insulinsecretory capacity was similar in islets from the LPP rats and the CP rats. Thus, short-term protein restriction did not alter the β-cell mass, which was due, in part, to reduced cell death by apoptosis during late pregnancy.